Improvement of the Mathematical Model for Determining the Length of the Runway at the Stage of Aircraft Landing. (2017) - Ugnenko, Evgeniya; Perova, Elena; Voronova, Yelizaveta; Viselga, Gintas
Abstract: The main methods for determining the length of the runway at the landing stage are shown in the given article. The shortcomings of these methods are proved. Statistical data that shows the need of landing distance recalculation for calculation of the required length of the runway are provided. The advanced mathematical model for calculating the required length of the runway at the landing stage is shown.